Death to fascism : Louis Adamic's fight for democracy - Enyeart, John P. (John Paul), 1970- (University of Illinois, 2019)
"The project aims to recover the story, work, and influence of Slovenian immigrant and influential author Louis Adamic. Between the mid-1920s and his death in 1951, Adamic published thirteen books and over 500 articles in magazines such as The Nation, Harper's and the Saturday Evening Post. Crowds filled venues across the U.S. to hear him speak. High school teachers and college professors assigned his work in their courses, he won major fellowships and book awards, he consulted with Presidents Roosevelt and Truman, and he even succeeded in shaping American foreign policy through his activism for Slavic issues. The story of Adamic points to and revives the many narratives that got overwritten as the grand narrative of the Cold War dominated history: resistance to fascism, transnationalism, and immigrant identity, to name a few. And there's even a mystery surrounding Adamic's death--suicide or murder? Alas, it will remain unsolved, but it points to the importance of the man and his work. Adamic helps us make sense of the importance of transnationalism in a period of massive immigration, labor upheaval, and confrontations between entrenched political interests"-- Provided by publisher
Keywords: Adamic, Louis, -- 1899-1951.; Adamic, Louis, -- 1899-1951 -- Political and social views.; Adamic, Louis, -- 1899-1951; Slovenian Americans -- Biography.; Historians -- United States -- Biography.; Social reformers -- United States -- Biography.; Anti-fascist movements -- United States.; Américains d'origine slovène -- Biographies.; Historiens -- États-Unis -- Biographies.; Réformateurs sociaux -- États-Unis -- Biographies.; Antifascisme -- États-Unis.; BIOGRAPHY & AUTOBIOGRAPHY -- General.; Anti-fascist movements; Historians; Political and social views; Slovenian Americans; Social reformers; United States; Electronic books.; Biographies